Changes in quality of sugar-cane juice upon delayed extraction and storage - Yusof, S.; Shian, L.S.; Osman, A. (Elsevier Science, 2000)
The quality of sugar-cane juice extracted from stored canes, as well as changes in quality of fresh juice stored at different temperatures, were studied. Cane stems were stored at 10±1°C, 85-88% relative humidity (RH) and 27±1°C, 55-85% RH, while fresh juice was stored at 5±1°C, 61-84% RH and 27±1°C, 55-85% RH. The physicochemical parameters evaluated were juice yield, juice colour, total soluble solids, sugar content (sucrose, fructose, glucose), titratable acidity, pH, chlorophyll content and sensory evaluation for colour and flavour. Viscosity and total microbial count on stored cane juice were also determined. Results showed that low temperature storage (10°C) of canes was able to maintain the quality of juice for up to 9 days while low temperature storage (5°C) of juice could last for only 4 days. During storage, sucrose contents decreased while fructose, glucose and titratable acidity increased in both types of samples. The colour changes in juice extracted from stored canes was inconspicuous until day 9. Deterioration of cane stored at 27±1°C occurred faster than that stored at 10±1°C. Fresh sugar-cane juice became spoiled after 4 days when stored at 5±1°C and 1 day when stored at 27±1°C. Microbial count, especially lactic acid bacteria count, increased during storage of cane juice.